Obstetrics Complications: Effects And Concerns At Komfo Anokye Teaching Hospital (Kath) - Helena Agyei (KNUST, 2025)
A THESIS SUBMITTED TO THE DEPARTMENT OF MATHEMATICS,KWAME NKRUMAH UNIVERSITY OF SCIENCE AND TECHNOLOGY IN PARTIAL FULFILLMENT OF THE REQUIREMENT FOR THE DEGREEOF M.PHIL MATHEMATICAL STATISTICS